The effects of oral hormone therapy in menopausal women on plasma fibrin polymerization and lysis - Borowiecka, Marta; Połać, Ireneusz; Kontek, Bogdan; Nowak, Paweł; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Objectives: Hormone therapy (HT) is more and more universally applied in treatment of menopausal age complaints. Thrombotic-embolic diseases are among the most dangerous and undesirable complications of HT. Hormones can lead to pro-thrombotic changes and the risk of thrombosis and its complications may be even 3-fold increased. Hormone therapy influences the metabolism of proteins participating in processes of clotting and lysis. The purpose of the research was to determine the long-term influence of HT on the kinetics of plasma fibrin polymerization and lysis in postmenopausal women. Material and methods: The material was fresh frozen plasma from 64 menopausal women either taking HT for 12 months (study group, n = 32) or with no treatment (controls, n = 32). For experiments thrombin was applied at the final concentration of 0.5 U/ml and tissue plasminogen activator (t-PA) at the final concentration of 60 ng/ml. Changes of turbidity were registered with a kinetic program for 55 minutes at λ = 415 nm. The maximum velocity of polymerization and half time of fibrin lysis were calculated. Results: Long-term HT treatment caused changes of fibrin plasma polymerization and fibrin lysis. The parameters of coagulation were increased and significant inhibition of lysis was noted in the women taking HT. Conclusions: 12 months of oral hormone therapy resulted in increased initial velocity of clot formation and inhibition of fibrinolysis. The increased level of fibrinogen and its higher polymerization may partly explain the increase in venous thrombosis and cardiovascular events reported after the use of combined hormone therapy.